Pengembangan Proyek Penguatan (P5) Dimensi Gotong Royong dengan Pendekatan STEAM di Sekolah Alam Dongi-Dongi - Riska Efendi; Arif Firmansyah; Muchdar; Kadek Hariana; Surahman; Rizal (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2026)
This study aims to develop the Pancasila Student Profile Strengthening Project (P5) focusing on the Mutual Cooperation Dimension using the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach. The P5 Project, with the Mutual Cooperation Dimension applied through an Entrepreneurship theme integrated with the STEAM approach, utilized the ADDIE development model, which involved expert validation for Material and Media, Product Testing, and Practicality Testing by teachers and students. The research subjects were 10 fourth-grade students at Sekolah Alam Dongi-dongi. Data were collected through observation, interviews, questionnaires, and documentation. The trial results indicated that the entrepreneurship project is valid and practical, and can enhance student engagement in learning. Furthermore, the project was effective in the teaching process with the help of volunteers, facilitating the understanding of complex materials, and ensuring that the learning not only provides immediate benefits but also promotes the sustainability of the school's ecosystem and its students. Therefore, this project is feasible for use in P5 learning at the elementary level, as it enriches students' learning experiences, increases creativity, fosters the spirit of mutual cooperation, and deepens their understanding of entrepreneurship.